Involvement of circRNAs in Proinflammatory Cytokines-Mediated β-Cell Dysfunction - Zhen Wang; Chao Deng; Ying Zheng (Mediators of Inflammation)
Aim. During the initial stage of type 1 diabetes, prolonged exposure of pancreatic β-cell to proinflammatory cytokines such as IL-1β, TNF-α, and IFN-γ results in a decreased capacity to produce and release insulin, as well as cell loss by apoptosis. Circular RNAs (circRNAs) are a new class of endogenous noncoding RNAs (ncRNAs) with closed loop with no free ends. circRNAs have been reported to be participated in the development of many diseases. As little is known about their role in insulin-secreting cells, this study is aimed at evaluating their contribution in the process of inflammation-induced β-cell damage. Methods. circRNA expression profile of MIN6 cells stimulated with a mix of cytokines, including IL-1β, IFN-γ, and TNF-α, was detected by circRNA microarrays. Four dysregulated circRNAs were validated by qRT-PCR. The involvement of the selected circRNAs in β-cell dysfunction was tested after their inhibition in MIN6 cells. MicroRNA target prediction software and multiple bioinformatic approaches were used to predict the targeting genes of circRNAs and analyze possible functions of the circRNAs. Results. 1020 upregulated and 902 downregulated circRNAs were identified in cytokines-treated β-cells. Inhibition of circRNAs 000286 and 017277 in β-cells could promote β-cell apoptosis and affect insulin biosynthesis and secretion. GO analysis enriched terms such as regulation of transcription and regulation of gene expression and KEGG analysis enriched top pathways included TGF-β and MAPK signaling pathways. Conclusions. The data shows that circRNAs may be involved in proinflammatory cytokines-mediated β-cell dysfunction and suggests the involvement of circRNAs in the development of type 1 diabetes.